Evaluation of the temporal acoustic window for transcranial doppler in a multi-ethnic population in Brazil - Bazan, Rodrigo [UNESP]; Braga, Gabriel Pereira [UNESP]; Luvizutto, Gustavo José [UNESP]; Hueb, João Carlos [UNESP]; Hokama, Newton Key [UNESP]; Zanati Bazan, Silméia Garcia [UNESP]; Carvalho Nunes, Hélio Rubens de [UNESP]; Leite, João Pereira; Pontes-Neto, Octávio Marques (Elsevier B. V., 2015)
The aim of this study was to relate the presence of a temporal acoustic window (TAW) to the variables sex, age and race. This observational study was conducted in patients under etiologic investigation after stroke, sickle-cell anemia and hospitalization in an intensive therapy neurologic unit. TAW presence was confirmed by bilateral assessment by two neurologists via transcranial Doppler (TCD). Multiple logistic regression was performed to explain the presence of the window as a function of sex, age and race. In 20% of the 262 patients evaluated, a TAW was not present. The incidence of TAW presence was greater in men (odds ratio [OR] = 5.4, 95% confidence interval [CI] = 2.5-11.7, p < 0.01); lower with increased age (OR = 0.9, 95% CI = 0.92-0.97, p < 0.01); and lower among those of African and Asian descent (OR = 0.32, 95% CI = 0.14-0.70, p = 0.005). On the basis of the results, more men than women had TAWs, and the decrease in TAWs was associated with increased age and African or Asian descent.
Keywords: Cerebrovascular diseases; Demographic data; Temporal acoustic window; Transcranial doppler